HUBUNGAN DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI WILAYAH KERJA PUSKESMAS TANJUNG MORAWA - Indah Permatasari; Mafe Robbi Simanjuntak; Tarianna Ginting (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2020)
Puskesmas is a place for health services in the form of health development which is responsible for the technical implementation unit of the District or City Service. Motivation and work discipline are factors that affect employee performance. Employee performance is real behavior that is displayed by employees as work performance that is generated in accordance with their position in a workplace. This research method used a cross sectional design with a total sampling of 50 respondents. The results of the study using the Chi-Square Test can be seen from the results of the statistical test for the work discipline variable, which has a p value of 0.02 0.05, so there is no relationship between work motivation and employee performance in the Tanjung Morawa Health Center work area.